A survey on robot fleet management systems for industrial processes - Gago, Reynaldo Mateus; Galassi, Mauricio; Silveira, Filipe; Freitas, Gustavo Medeiros (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
The increasing deployment of industrial and service robots has created a significant demand for robotic Fleet Management Systems (FMS) to control these assets and deliver efficient and safe operations. This paper explores applications of FMS across various industrial sectors, including oil and gas, mining and agroindustry. Then, it describes expected functionalities of FMS, such as route planning, task allocation, simulation, realtime monitoring, integration with corporate systems, diagnosis, teleoperation, data analytics and devops tools. The discussion includes an analysis of current FMS software solutions, highlighting their features and industry-specific applications. The paper concludes that the continued evolution of FMS technology is critical for optimizing robotic operations and achieving strategic industrial goals, and the selection of a FMS solution should consider companies’ current fleet and expectations towards its adoption.